Binding “When” and “Where” Impairs Temporal, but not Spatial Recall in Auditory and Visual Working Memory - Delogu, Franco; Postma, Albert; Nijboer, Tanja C.W. (Frontiers in Psychology, 2012)
Information about where and when events happened seem naturally linked to each other, but only few studies have investigated whether and how they are associated in working memory. We tested whether the location of items and their temporal order are jointly or independently encoded. We also verified if spatio-temporal binding is influenced by the sensory modality of items. Participants were requested to memorize the location and/or the serial order of five items (environmental sounds or pictures sequentially presented from five different locations). Next, they were asked to recall either the item location or their order of presentation within the sequence. Attention during encoding was manipulated by contrasting blocks of trials in which participants were requested to encode only one feature, to blocks of trials where they had to encode both features. Results show an interesting interaction between task and attention. Accuracy in the serial order recall was affected by the simultaneous encoding of item location, whereas the recall of item location was unaffected by the concurrent encoding of the serial order of items. This asymmetric influence of attention on the two tasks was similar for the auditory and visual modality. Together, these data indicate that item location is processed in a relatively automatic fashion, whereas maintaining serial order is more demanding in terms of attention. The remarkably analogous results for auditory and visual memory performance, suggest that the binding of serial order and location in working memory is not modality-dependent, and may involve common intersensory mechanisms.